Details of Walker 256 carcinosarcoma growth in Brattleboro and ISIAH lines of rats - I. I. Khegay (Вавиловский журнал генетики и селекции)
The growth dynamics of transplantable Walker 256 carcinosarcoma was investigated in rats modeling inherited systemic pathological processes. Hypothalamic diabetes insipidus is developing in Brattleboro rats on the background of total vasopressin absence in the blood. Regulation of water-electrolytic metabolism is disturbed due to hormonal disbalance. ISIAH rats are carriers of inherited stress-induced arterial hypertension. Vascular rigidity is accompanied by additional pleiotropic effects. The experiments have been carried out on inbred Brattleboro and ISIAH rats, and their hybrids segregated from (ISIAH × Brattleboro) F1 × Brattleboro mating. The mutant vasopressin gene di (diabetes insipidus) and fur painting genes, albino (C) and hooded (h), localized in three different linkage groups, were used as genetic markers of progeny splitting. Alternative pairs of traits were: daily water consumption above 45 % or lower than 20 % of body weight – for the vasopressin locus; total white or other color of fur – for the albino locus; presence or absence of unevenness in fur painting – for the hooded locus. It has been found that there are only two types of growth dynamics of grafted tumor. In the rats of the inbred Brattleboro line and in the didi homozygotes, which were segregated from analytical mating (ISIAH × Brattleboro) F1 × Brattleboro, tumor began to regress and diminished until absolute disappearance after some initial growing. Heterozygous offspring di+ and parental ISIAH rats with the normal vasopressin genotype (++) showed permanent tumor growth until lethal injury. It was found that tumor regression demonstrates concordance exclusively to the didi genotype, segregation of this feature does not depend on the genotype of the albino or hooded loci. Alternative to tumor regression, permanent growth of tumor is observed in all rats having at least one normally expressed vasopressin gene.